2022
DOI: 10.3390/su142013037
|View full text |Cite
|
Sign up to set email alerts
|

What Causes Burnout in Special School Physical Education Teachers? Evidence from China

Abstract: Special physical education is considered a challenging process concerned with the development of the physical and mental health of students with physical disabilities. Special physical education teachers face pressures from society, parents, schools, and themselves, which can easily lead to burnout and increase levels of teacher attrition. In our paper, we explore the significant effects of role and job stress (divided into role ambiguity and conflict, and stressors and stress responses, respectively), teachin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…al (2014), conducted a survey on four different real estate companies and found that employees' pursuit of soft influencing factors in the work environment is higher than that of hard influencing factors. Sang et. al (2022), conducted a survey on college physical education teachers in Henan Province, analyzing the differences in demographic variables among college physical education teachers, and found that the school environment has an impact on employee job performance.…”
Section: Resultsmentioning
confidence: 99%
“…al (2014), conducted a survey on four different real estate companies and found that employees' pursuit of soft influencing factors in the work environment is higher than that of hard influencing factors. Sang et. al (2022), conducted a survey on college physical education teachers in Henan Province, analyzing the differences in demographic variables among college physical education teachers, and found that the school environment has an impact on employee job performance.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, job stress is a risk variable for burnout (Chen et al, 2022; X. Li et al, 2021; Sang et al, 2022). Job stress is an unpleasant negative emotional experience for teachers that can lead to excessive physical and mental fatigue, distress, nervousness, or frustration (Roeser et al, 2013; W.…”
Section: Literature Reviewmentioning
confidence: 99%